Almost Periodic Solutions of a Discrete Mutualism Model with Variable Delays - Yongzhi Liao; Tianwei Zhang (Discrete Dynamics in Nature and Society)
We discuss a discrete mutualism model with variable delays of the formsN1(n+1)=N1(n)exp{r1(n)[(K1(n)+α1(n)N2(n-μ2(n)))/1+N2(n-μ2(n)))-N1(n-ν1(n))]}, N2(n+1)=N2(n)exp{r2(n)[(K2(n)+α2(n)N1(n-μ1(n)))/(1+N1(n-μ1(n)))-N2(n-ν2(n))]}. By means of an almost periodic functional hull theory, sufficient conditions are established for the existence and uniqueness of globally attractive almost periodic solution to the previous system. Our results complement and extend some scientific work in recent years. Finally, some examples and numerical simulations are given to illustrate the effectiveness of our main results.